Bordering Beyond Borders: A Governmentality Analysis of Australia’s Operation Sovereign Borders and Israel’s Externalisation of Asylum Policy - Titan Alramadhan (WIMAYA, 2025)
This paper analyses how Australia and Israel transform deterrence into an ethical means of moral control; it investigates how these nations are using the concept of "care" in order to rationalise their strict border management practices. Through its analysis of Australia's Operation Sovereign Borders and Israel's externalisation policies, this paper demonstrates how the act of coercion can be disguised as compassionate action, and exclusionary actions are portrayed as protective actions. This paper utilises the theoretical framework of Foucauldian governmentality to illustrate how the Australian and Israeli governments utilise moral reasoning to govern asylum seekers; they merge authority with empathy, and both appear to be one and the same. Furthermore, this paper illustrates that while deterrence may work through physical force, it also works by the notion that controlling movement is an ethically responsible obligation. Both instances demonstrate how morality is used as a mechanism of power and how humanitarian language serves as an exclusionary device. Thus, by demonstrating how such practices occur, this paper aids in explaining how the discourse of care has become a core aspect of the global governance of mobility.